PDF Influence of Er:Cr;YSGG laser Desensitization on SBS of resin cement to dentin - Mubaraq, Rusul Mohammed; Basima Mohammed Ali Hussein (Iraqi Journal of Laser, 2022)
Background: Crown preparation of vital teeth involve the removal of a sound tooth structure, and when enamel removed this lead to exposed dentin with an   increase in the number of open dentinal tubules also the diameter of dentinal tubules will increase, furthermore lead to increase movement of fluids inside the tubules all that causes post preparation sensitivity. The aim of this study is to evaluate the effect of desensitizing by Er:Cr:YSGG laser on shear bond strength of prepared tooth and resin cement. Materials and methods: Thirty sound maxillary premolars, grouped into three groups(n=10). Group A is the control group, group B irradiated by Er:Cr:YSGG laser with (0.25 W, 20 Hz, 10%water and air), group C irradiated by Er:Cr:YSGG laser with (0.5 W, 20 Hz, 10% water and air). Results: SEM examination showed complete occlusion of opened dentinal tubules after laser irradiation of both groups that irradiated with laser. Statistical analysis showed significant increase in surface roughness in group B and C. SBS was significantly increase in group B with no significant increase in group C. Conclusion: Er:Cr:YSGG laser can occlude open dentinal tubules without and adverse effect on the retention of the restoration, on the contrary it increase bonding strength. And this increasing was significant in group B with (0.25W, 20 Hz, 10 % water and air). suggestion: so the parameters used in group B (0.25 W, 20Hz, 10 % water and air) is recommended for desensitizing prepared tooth and induce enhancement to the bonding strength of resin to tooth surface.